Expedition to Blue Cave - Decter, Ed 1959- (Aladdin Paperbacks, an imprint of Simon & Schuster, 2007)
Cam, Shelby, and their friends sail for Blue Cave to observe rare bioluminescent plankton but instead discover a pair of crooks who are hiding an antique golden sextant stolen from rich Mr. Thorpe. When the boys recover the stolen goods, the crooks kidnap Shelby's little sister
Keywords: Adventure and adventurers / Fiction; Adventure stories / Juvenile fiction; Explorers / Juvenile fiction